Pricing of settlement link services and mergers of central securities depositories - Jens Tapking (European Central Bank (ECB), 2007)
This paper tries to contribute to the discussion on the role of securities settlement infrastructures for financial integration in Europe. It presents a model that can explain a well-known stylized fact of securities settlement, the surprisingly high fees charged by central securities depositories (CSDs) for settlement through links between CSDs. As the model turns out to provide a robust explanation for this stylized fact, it is then used to analyzes an important policy question, the welfare effects of mergers of CSDs.
Keywords: G21; G15; L13; 330; central securities depositories; link settlement fees; Securities settlement; Wertpapierhandel; Bankentgelt; Wertpapierdepot; Unternehmenskonzentration; EU-Staaten